Bread baking: Technological considerations based on process modelling and simulation - Purlis, Emmanuel (2011)
This paper presents a study of bread baking, mainly from a technological point of view, i.e. focused on transport phenomena and major quality changes occurring during the process. Such study was carried out by numerical simulation of a previously developed and validated mathematical model, which describes the simultaneous heat and mass transfer (with phase change in a moving boundary) taking place in bread during baking. Kinetic models for starch gelatinization and browning development were coupled to the transport model. Input variables to the model were oven temperature, heat transfer coefficient, and bread radius. A total of 105 operating conditions were simulated using the finite element method, and the end point of baking was established for three values of surface lightness. It is shown that an intense heating strategy can produce a browned but unbaked product, besides nutritional quality is negatively affected. Furthermore, minimization of baking time is restricted by internal resistance to heat transfer.